2008
DOI: 10.1038/nature07313
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A confers receptor-activated calcium-dependent chloride conductance

Abstract: Calcium (Ca(2+))-activated chloride channels are fundamental mediators in numerous physiological processes including transepithelial secretion, cardiac and neuronal excitation, sensory transduction, smooth muscle contraction and fertilization. Despite their physiological importance, their molecular identity has remained largely unknown. Here we show that transmembrane protein 16A (TMEM16A, which we also call anoctamin 1 (ANO1)) is a bona fide Ca(2+)-activated chloride channel that is activated by intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,445
12
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,180 publications
(1,552 citation statements)
references
References 41 publications
68
1,445
12
6
Order By: Relevance
“…It was first described as a calcium-activated chloride channel in 2008 and is routinely used in the diagnosis of gastrointestinal stromal tumours (GIST) [10][11][12][13][14][15][16]. Its expression pattern in salivary gland neoplasms is not well established although a recent study showed expression in acinar lumens in both normal glands and ACC [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was first described as a calcium-activated chloride channel in 2008 and is routinely used in the diagnosis of gastrointestinal stromal tumours (GIST) [10][11][12][13][14][15][16]. Its expression pattern in salivary gland neoplasms is not well established although a recent study showed expression in acinar lumens in both normal glands and ACC [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This, in combination with the low Ca 2+ sensitivity of ANO1 channels (EC 50 at negative voltages is ∼2–5 μ m; Yang et al . 2008; Xiao et al . 2011), would make them insensitive to ‘distal’ Ca 2+ elevations.…”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%
“…−60 to −100 mV) were reported to be in the range of 3–5 μ m while at high, depolarizing voltages the EC 50 is about tenfold lower (Yang et al . 2008; Xiao et al . 2011).…”
Section: Ano1 Containing Signalling Complexes: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations